Destined for you ebook - Peterson, Tracie (Ladies of the Lake., 2021)
After scarlet fever kills her mother and siblings, Gloriana Womack is dedicated to holding together what's left of her fractured family. Luke Carson arrives in Duluth to shepherd the construction of the railroad and reunite with his brother. When tragedy strikes and Gloriana and Luke must help each other through their grief, they find their lives inextricably linked.